Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1742-2094-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib reduces brain dopaminergic neuronaldysfunction, and improves sensorimotor behavioral performance in neonatal rats exposed to systemic lipopolysaccharide

Abstract: BackgroundCyclooxygenase-2 (COX-2) is induced in inflammatory cells in response to cytokines and pro-inflammatory molecules, suggesting that COX-2 has a role in the inflammatory process. The objective of the current study was to examine whether celecoxib, a selective COX-2 inhibitor, could ameliorate lipopolysaccharide (LPS)-induced brain inflammation, dopaminergic neuronal dysfunction and sensorimotor behavioral impairments.MethodsIntraperitoneal (i.p.) injection of LPS (2 mg/kg) was performed in rat pups on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 51 publications
3
48
1
Order By: Relevance
“…This demonstrates the sensorimotor deficiencies in early postnatal days in rats. It was reported that such deficits in sensorimotor activity are likely caused by subcortical damage in the neonatal brain (Fan et al 2005;Kaizaki et al 2013). The loss in sensorimotor function was observed when there was also loss of mitochondrial function post second episode of anoxia, but not after first episode.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This demonstrates the sensorimotor deficiencies in early postnatal days in rats. It was reported that such deficits in sensorimotor activity are likely caused by subcortical damage in the neonatal brain (Fan et al 2005;Kaizaki et al 2013). The loss in sensorimotor function was observed when there was also loss of mitochondrial function post second episode of anoxia, but not after first episode.…”
Section: Discussionmentioning
confidence: 94%
“…The loss in sensorimotor function was observed when there was also loss of mitochondrial function post second episode of anoxia, but not after first episode. Therefore, our results indicate that in anoxic condition mitochondrial bioenergetics plays an important role in development of sensorimotor functions (Kaizaki et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…These effects are likely to be associated with the neuroprotective activity of celecoxib (Hunter et al, 2007;López-Villodres et al, 2012;Kaizaki et al, 2013). We observed that celecoxib reduced glutamate release from nerve terminals, and this effect was dose-dependent and peaked at 30 mM with an IC 50 of 7 mM.…”
Section: Inhibition Of Glutamate Release By Celecoxibmentioning
confidence: 64%
“…anti-inflammatory activity, and its neuroprotective action is generally assumed to be associated with this property (Hunter et al, 2007;López-Villodres et al, 2012;Kaizaki et al, 2013). However, the pharmacological mechanisms underlying the neuroprotective effects of celecoxib have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation